Persepsi Pengguna Jasa Transportasi Online Grab Ditinjau dari Kualitas Pelayanan - Muhammad Syahrul; Nur Arisah; Muhammad Ilyas Thamrin Tahir (Journal of Economic Education and Entrepreneurship Studies, 2020)
This study aims to determine the quality of Grab online transportation services according to the perceptions of students of the Faculty Economics, in terms of the dimensions of Tangible, Reliability, Responsiveness, Assurance and Emphaty, and to find out which dimensions of service quality most influence student satisfaction in using online transportation services. This type of research is descriptive qualitative using observation, interview, and documentation techniques in data collection. The informants in this study were three people with the data analysis technique used, namely the interactive model analysis technique and the triangulation technique. The results obtained are the perceptions of users of Grab online transportation services, especially students of the Faculty of Economics, Makassar State University, are considered to be quite good. This can be seen from the various services in the application system, as well as transparent and affordable prices, and promos that are always provided by the company. They also have a friendly attitude, alertness, and the professionalism of Grab riders/drivers is quite good. It's just that there still needs to be an update to the application that must be improved, for example the reading of points/locations is sometimes incorrect and it is hoped that Grab online transportation will pay more attention to the standardization of driver/driver vehicles, as well as the need to limit working operating hours for Grab riders/drivers themselves.